Tři báze modelu rozvoje regionu - Kraftová, Ivana (Univerzita Pardubice, 2010)
The submission pays attention to a model of region development as a fundamental attribute of CR and EU regional politics. It focuses on endogenous development factors, which are clustered into three bases: infrastructure, production and consumption. It shows their impact on development of selected indicators of region competitiveness – relations among regional GDP per capita, rate of regional GDP growth, investments (gross formation of fixed capital), and net disposable income households on the Pardubice region´s case.
Keywords: model of region development; infrastructure; production; consumption; region competitiveness